Change of gut microbiome structure in preterm infants with hypoxic ischemic encephalopathy induced by apnea - Guang Chen; Fengdan Li; Jiwei Du (Pediatrics and Neonatology)
Background: Since a high incidence of mortality and morbidity is induced by preterm birth, it is important to understand how hypoxic ischemic encephalopathy (HIE) in preterm infants alters gut microbiota development. Methods: We analyzed 89 stools from 30 term newborns (NNG), 30 preterm infants without apnea (PG) and 29 preterm infants with definite diagnosis of apnea (PAG) by 16S rRNA gene sequencing in this study. Results: The data showed that species richness and diversity in PG and PAG were significantly lower compared with NNG. This study investigated the difference in bacteria and relative abundance between NNG, PG and PAG. The abundance of Klebsiella and Streptococcus strains were markedly increased, while Clostridium was significantly decreased in PAG compared with PG. The most notable exceptions included Klebsiella pneumoniae and Escherichia coli, which were markedly increased in PG and PAG, and these provide the main bacterial source of dopamine and serotonin production. This study also revealed that Lactobacillus and Bifidobacterium were markedly increased in PG and PAG, and these are the main source of GABA production for bacteria. Conclusion: The present study confirmed that apnea had a uniform effect on species richness and diversity. However, it cannot be established whether the abundance and difference of these bacterial genera and species directly affect the occurrence and development of preterm infants with HIE by secreting intestinal neurotransmitters.